(Zanemarena) uloga i važnost društvenih normi u poticanju međugrupnog kontakta : pregled dosadašnjih nalaza i istraživački izazovi - Pehar, Lana (Array, 2018)
Although social norms have a strong influence on attitudes and behaviours in different social situations, their research and practical use are significantly limited by inconsistencies of how different types of norms have been defined and measured. In an attempt to reach a common, comprehensive definition of social norms, in this paper we describe the most important conceptualizations and types of norms developed within different theoretical approaches and give an overview of relevant research of normative influences on individual and intergroup behaviours. In addition, this review especially focuses on ingroup norms about intergroup contact as a specific type of norm that describes and prescribes typical and appropriate interactions with outgroup members. In this regard, this review represents an important systematization since ingroup contact norms, despite being long recognized as important regulators of intergroup relations, have been neglected so far both as a research and as a theoretical construct. Therefore, we present the results of scarce new research on relationships between different types of contacts among members of different groups, in group contact norms, and intergroup outcomes, in order to highlight and clarify various roles that ingroup contact norms may play in shaping complex dynamics of relationships between social groups. Finally, we underline unresolved issues and offer possible directions for future research.